2002
DOI: 10.1093/jn/131.10.3155
|View full text |Cite
|
Sign up to set email alerts
|

Human Adenovirus Ad-36 Promotes Weight Gain in Male Rhesus and Marmoset Monkeys

Abstract: Although obesity has multiple etiologies, an overlooked possibility is an infectious origin. We previously identified two viruses, SMAM-1, an avian adenovirus (Ad), and Ad-36, a human adenovirus, that produce a syndrome of visceral obesity, with paradoxically decreased serum cholesterol and triglycerides in chickens and mice. In the two studies presented in this paper, we used nonhuman primates to investigate the adiposity-promoting potential of Ad-36. In study 1, we observed spontaneously occurring Ad-36 anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
206
2
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(224 citation statements)
references
References 16 publications
7
206
2
7
Order By: Relevance
“…Of these, SMAM-1, an avian adenovirus was the first to show an association with human obesity 14 and Ad-36, a human adenovirus was the first human virus reported to cause adiposity in animal models and show association with human obesity. [1][2][3][4] As these initial reports, adipogenic potentials of more human adenoviruses, Ad-37 and Ad-5, have been reported. 6,15 Potential of various human adenoviruses to increase preadipocyte differentiation and cause adiposity may vary.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Of these, SMAM-1, an avian adenovirus was the first to show an association with human obesity 14 and Ad-36, a human adenovirus was the first human virus reported to cause adiposity in animal models and show association with human obesity. [1][2][3][4] As these initial reports, adipogenic potentials of more human adenoviruses, Ad-37 and Ad-5, have been reported. 6,15 Potential of various human adenoviruses to increase preadipocyte differentiation and cause adiposity may vary.…”
Section: Discussionmentioning
confidence: 82%
“…[1][2][3][4] Inoculation of 3T3-L1 preadipocytes with Ad-36, but not Ad-2 (a nonadipogenic human adenovirus), resulted in increased adipocyte number, cellular lipid accumulation and glycerol 3-phosphate dehydrogenase levels (GPDH; an adipocyte differentiation specific enzyme marker) and modulation of several key cellular genes of differentiation. 5 The absence of adipogenic effect of Ad-2 in animals and cells 5,6 and a lack of association with human obesity 1 suggested that the lipogenic potential is not a common characteristic of all adenoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…This initial finding has now been extended to other species, including mice, primates, canine and possibly humans, with a range on animal and human viruses, including canine distemper virus, Rous-associated virus 7, Borna disease virus, SMAM-1 and Ad36. [5][6][7][8][9][10][11][12][13] In the present study, we have shown that the potential gene therapy viral vector Ad5 also leads to increase body adiposity in mice. Ad5-treated animals were shown to gain more weight over the 21 weeks following inoculation than saline-treated animals.…”
Section: Discussionmentioning
confidence: 95%
“…Increased adiposity has been observed in animal models following infection with animal viruses, canine distemper virus, [2][3][4][5] Rous-associated virus, 6,7 Borna virus, 8 an avian adenovirus, SMAM-1 9,10 and, also, with the human virus adenovirus 36 (Ad36). [11][12][13] Of these, SMAM-1 and Ad36 have been associated with human obesity: increased level of antibodies for these viruses has been found in human subjects who were obese. 14,15 Ad36 produces a syndrome of visceral obesity in chickens and mice, both hyperplastic and hypertrophic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Data from studies in animals indicate a possible role for virus infections in the etiology of human obesity. [19][20][21] Moreover, Ad-36 is associated with increased body weight and paradoxically lower cholesterol and triglyceride levels in Ad-36 antibody-positive vs -negative subjects. 22 Therefore it can be hypothesized that (chronic) virus infections induce adipocyte dysfunction thus leading to the development of diabetes mellitus and/or cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%